The Analysis of Moral Values Found in Shah Rukh Khan's Speech at the University of Edinburgh's New College - Imtihan Hanim (Edelweiss : Journal Of Innovation In Educational Research, 2025)
Abstract The purpose of the research is to outline the values found from Shah Rukh Khan’s speech at the University of Edinburgh’s New College in 2015. This study employs a descriptive and qualitative methodology, drawing on Hornby’s moral values theory to determine the form of values in each sentence, phrase, and clause that Shah Rukh Khan lectured. The result showed that there were 6 of the 11 types of moral values captured. The six kinds of moral values have been established by this study cover thankfulness, bravery, humbleness, kind-hearted, steadfastness, and love and affection. The most dominant values captured in Shah Rukh Khan’s speech is bravery, captured in 5 utterances. Keywords: Speech, Moral, Values, Analysis